EVALUASI PROGRAM SANITASI BERBASIS MASYARAKAT (SANIMAS) DI KECAMATAN KEDIRI KABUPATEN TABANAN - Dewi, Putu Ayu Ari Puspita; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Community-Based Sanitation (SANIMAS) is a program organized to increase access to sanitation related to wastewater extraction in residential areas with slums, densely populated, and prone to sanitation. This study aims to evaluate the Community Based Sanitation Program (SANIMAS) in Kediri District, Tabanan Regency. This research is a qualitative research with descriptive analysis. The data used are primary and secondary data. This research is located in 2 villages in Kediri District, Tabanan Regency. The results showed that the management of the WWTP in the SANIMAS program that had been built in the three KSMs was not optimal due to the lack of management and maintenance on the part of the manager and the lack of awareness of the WWTP users. In addition, the results of laboratory tests at the three locations showed that the two locations had COD values above the established quality standards. Therefore it is necessary to carry out routine management and maintenance to overcome this as well as regular monitoring for program sustainability. Keywords: Evaluation, Community-Based Sanitation, Wastewater Treatment Plant